2017
DOI: 10.1001/journalofethics.2017.19.4.pfor1-1704
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Physicians and Health Care Systems in “Difficult” Clinical Encounters

Abstract: Physicians are, by definition, contributing partners in "difficult" patientphysician encounters. Although research on relevant physician qualities is limited, common themes mirror the more extensive literature on physician burnout. Focusing on primary care, we discuss physician-level factors in difficult encounters related to psychosocial attitudes and selfawareness, communication skills, and practice environments. Potential approaches to mitigating these factors include changes to medical training, such as st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
2
0
4
Order By: Relevance
“…Our study results are consistent with prior studies that have identified S-T workplace factors such as lack of time to exercise ( Olson et al, 2014 ), time spent on EHR documentation ( Adler-;Milstein et al, 2020 ),( Rotenstein et al, 2018 ), time spent on tasks related to case management( Moy et al, 2021 ) and lack of collaborative patient care as determinants ( Zubatsky et al, 2018 ) of provider burnout. Furthermore, some S-T workplace factors like frequent pages or interruptions for non-emergent issues( Witherspoon et al, 2019 ) and difficult interactions with patients or families ( Goldsmith and Krebs, 2017 ; Wolkenstein and Moffic, 2019 ) have been explored in previous studies but their association with burn out in hospitalists hasn't been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Our study results are consistent with prior studies that have identified S-T workplace factors such as lack of time to exercise ( Olson et al, 2014 ), time spent on EHR documentation ( Adler-;Milstein et al, 2020 ),( Rotenstein et al, 2018 ), time spent on tasks related to case management( Moy et al, 2021 ) and lack of collaborative patient care as determinants ( Zubatsky et al, 2018 ) of provider burnout. Furthermore, some S-T workplace factors like frequent pages or interruptions for non-emergent issues( Witherspoon et al, 2019 ) and difficult interactions with patients or families ( Goldsmith and Krebs, 2017 ; Wolkenstein and Moffic, 2019 ) have been explored in previous studies but their association with burn out in hospitalists hasn't been firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…En el ámbito sociocultural hubo situaciones de estigma laboral, social y familiar por el burnout, como causa y consecuencia, es decir, el estigma que vivieron los profesionales por atender a pacientes afectados con la Covid-19 favoreció la aparición o el desarrollo del burnout, pero también los profesionales que padecieron el síndrome se sintieron estigmatizados, señalados y aislados. De igual forma, se reportó, tanto en médicos como en enfermeras, un deterioro de sus relaciones interpersonales, familiares y de parejas, lo incrementó el número de divorcios, así como la disfunción familiar (32,48,49). Algo similar sucedió con el reconocimiento del trabajo de la mujer en el sector salud, como causa y consecuencia, es decir, las que padecían burnout consideran que su estado de agotamiento laboral ocasionó un menor reconocimiento (28,50), pero también, ser poco reconocidas fue un factor que favoreció el desarrollo de este síndrome (20,21,50,51).…”
Section: Subtema 3 Consecuencias Del Burnoutunclassified
“…Dificultades en las relaciones profesionales, familiares y de parejas, y aumento de los divorcios (20,32,39,47,48) Sistema integral de calidad Calidad y seguridad en la atención…”
Section: Relaciones Interpersonalesunclassified
See 1 more Smart Citation
“…Weaker therapeutic alliances may form, whether due to institutional policy (Back et al, 2009) or the withdrawal from relationship by HCP (Huff et al, 2015;Mack et al, 2009), resulting in feelings of abandonment among both patients and their families. During EOL, the established traditional boundaries (etiquettes, rituals, and behaviors) associated with patient and provider become difficult to achieve (Goldsmith & Krebs, 2017;West et al, 2018) and often need to be crossed or modified.…”
Section: Patient-provider Relationship and Therapeutic Alliancementioning
confidence: 99%